Unusual cranial and abdominal computed tomographic (CT) scan appearances in a case of systemic lupus erythematosus (SLE). Issue 2 (February 1987) - Boulter, M; Brink, A; Mathias, C; Peart, S; Stevens, J; Stewart, G; Unwin, R
Abstract : A 35 year old woman presented with headache and fever. Computed brain tomography showed diffuse low attenuation in the cerebral white matter. Several months later, serological tests for systemic lupus erythematosus (SLE) became positive. In spite of immunosuppressive therapy she relapsed after six months of treatment, presenting with abdominal symptoms and signs. On this occasion an abdominal CT scan showed distended and oedematous loops of bowel attributed to an underlying vasculitis. This case illustrates novel CT scan appearances in two systems involved in SLE.